Reduction of Free Fatty Acids, Safety, and Pharmacokinetics of Oral GS‐9667, an A1 Adenosine Receptor Partial Agonist. (6th April 2013) - Staehr, Peter M.; Dhalla, Arvinder K.; Zack, Julia; Wang, Xuegong; Ho, Yu L.; Bingham, Justus; Belardinelli, Luiz
Abstract: GS‐9667, a new selective, partial agonist of the A1 adenosine receptor (AR), may represent an effective therapy for Type 2 diabetes (T2DM) and dyslipidemia via lowering of free fatty acids (FFA). The objectives of the studies were to evaluate the effects of single and multiple doses of GS‐9667 on plasma FFA concentrations, its pharmacokinetics (PK) and safety/tolerability. Two studies were conducted. In the single ascending dose study, healthy, non‐obese, and obese subjects received a single oral dose of GS‐9667 (30–1 800 mg). In the multiple, ascending dose study, healthy, obese subjects received GS‐9667 (600–2 400 mg QD, 1 200 mg BID, or 600 mg QID) for 14 days. Blood and urine samples were collected for lipid profiling and PK analyses. The ECG, vital signs, and subject tolerability were monitored. Doses of GS‐9667 ≥300 mg caused dose‐dependent reductions in FFA levels that were reproducible over 14 days without evidence of desensitization or rebound. All doses were well tolerated. GS‐9667 was rapidly absorbed and distributed; Steady‐state concentrations were achieved within 3–5 days. The A1 AR partial agonist GS‐9667 reduced plasma FFA, exhibited linear kinetics, and was well‐tolerated in healthy non‐obese and obese subjects.